A formação do professor do ensino religioso: um novo olhar sobre a inclusão de alunos com deficiência na escola - Bastos, Ana Cristina de Almeida Cavalcante (2015)
Religious Education, regulated by Law 9.475/97, as an integral part of the basic education of citizens is a privileged locus for promotion of cultural recognition and assumption of people belonging to minorities, among them people with disabilities, because they present a long-term impairment of physical, intellectual or sensory nature, they are more susceptible to situations of exclusion. Thus, this research has as main objective to investigate the importance of the religious education teacher in special/inclusive education, from the perspective of human rights, in order to strengthen the inclusion process of students with disabilities in school. And the following objectives: contextualize the phenomenon of exclusion/inclusion of persons with disabilities in the mythical and historical time, and the exclusion is evidenced most visibly over time in socioeconomic, religious and education of such persons; present guiding documents aimed at inclusive education, religious education and human rights at the international and national level, seeking dialogue with these three areas of knowledge aiming at the reasoning of including students with disabilities in school; and outline the necessary knowledge for inclusive teaching from the perspective of human rights, with a religious education teacher profile reasoned from the Pedagogy of Autonomy. The dissertation was structured containing an introduction - Through the windows of the soul: resignifying looks! - Three chapters: (1) a glance at the time: the journey between exclusion and inclusion of people with disabilities to stand as a subject of rights; (2) a cutout on the look religious education: leaving the exclusion of proselytizing for the visibility of minorities! (3) The training of religious education teachers from the perspective of human rights: expanding the focus of the look; and the final considerations: a new look on the inclusion of disabled students in school. This study was conducted with a methodological approach as a theoretical-methodological documental and bibliographic research on special/inclusive education, religious education and human rights, always seeking to promote the interface between knowledge, and diversity as a guiding principle. Authors such as Santiago (2011), Silva (2009), Freire (1996; 2002), Holmes (2010), Souza (2013), Escarião (2009; 2013), Frankl (1991), Martins (1997) Junqueira (2009; 2011) Passos (2007) Gonsalves (2012; 2015a; 2015b) and others contributed to the theoretical framework.Because Religious Education has its National Curriculum Parameters - PCNER's grounded on the principles of citizenship, respect for diversity, tolerance in understanding the other and the relationship of human beings in their quest for the transcendent and within an epistemological and pedagogical vision to stand against situations of prejudice and intolerance, it becomes an appropriate curricular component to bring up issues related to inclusive education, since this also features respect for diversity as one of its guiding principle.The relevance of this research is to provoke reflections on the specific role that the teacher of Religious Education can play as a facilitator of inclusive education regarding the inclusion of students with disabilities in an open and pluralistic school, geared towards ensuring not only access for all students but to successfully remain in school.